A dual deformable liposomal ointment functionalized with retinoic acid and epidermal growth factor for enhanced burn wound healing therapy. (27th March 2019) - Lu, Kong-Jun; Wang, Wei; Xu, Xiao-Ling; Jin, Fei-Yang; Qi, Jing; Wang, Xiao-Juan; Kang, Xu-Qi; Zhu, Meng-Lu; Huang, Qiao-Ling; Yu, Chao-Heng; You, Jian; Du, Yong-Zhong
Abstract : A dual deformable liposomal ointment functionalized with TRA and EGF remarkably promoting wound healing. Abstract : An ointment containing retinoic acid deformable liposomes (TRA DLs) and epidermal growth factor cationic deformable liposomes (EGF CDLs) was prepared for the treatment of deep partial-thickness burns. The characterization tests confirmed both liposomes featured small particle sizes, high drug entrapment efficiencies and sustained drug release behavior. Compared with the free drug, TRA DLs and EGF CDLs exhibited superior skin permeation and remarkably increased drug deposition by 2.9 and 18.8 folds, respectively. Results on HaCaT cells indicated the combined application of two liposomes exerted a synergistic effect and prominently promoted cell proliferation and migration. Application of the dual liposomal ointment on a deep partial-thickness burn model stimulated wound closure ( p < 0.001), promoted skin appendage formation and increased collagen production, thus improving healing quality. Finally, it was demonstrated that TRA significantly up-regulated the expression of EGFR and HB-EGF to enhance the therapeutic effect of EGF. Therefore, the dual liposomal ointment is a promising topical therapeutic for burn treatment.